Linker histones and chromatin remodelling complexes maintain genome stability and control cellular ageing. (January 2019) - Miloshev, George; Staneva, Dessislava; Uzunova, Katya; Vasileva, Bela; Draganova-Filipova, Milena; Zagorchev, Plamen; Georgieva, Milena
Highlights: Hho1p interaction with Arp4p is crucial for yeast CLS. Premature ageing phenotype is triggered by abrogation of Hho1p and Arp4p interaction. The cells without the linker histone and with a mutation in Arp4p die young. Chromatin mutants possess abnormal vacuolar morphology at earlier stages of their CLS. Abnormal chromatin structure makes cells prone to stress. Abstract: Linker histones are major players in chromatin organization and per se are essential players in genome homeostasis. As the fifth class of histone proteins the linker histones not only interact with DNA and core histones but also with other chromatin proteins. These interactions prove to be essential for the higher levels of chromatin organization like chromatin loops, transcription factories and chromosome territories. Our recent results have proved that Saccharomyces cerevisiae linker histone – Hho1p, physically interacts with the actin-related protein 4 (Arp4) and that the abrogation of this interaction through the deletion of the gene for the linker histone in arp4 mutant cells leads to global changes in chromatin compaction. Here, we show that the healthy interaction between the yeast linker histone and Arp4p is critical for maintaining genome stability and for controlling cellular sensitivity to different types of stress. The abolished interaction between the linker histone and Arp4p leads the mutant yeast cells to premature ageing phenotypes. Cells die young and are more sensitive to stress. These results unambiguously prove the role of linker histones and chromatin remodelling in ageing by their cooperation in pertaining higher-order chromatin compaction and thus maintaining genome stability.